World news in Indian newspapers, 1782-1908. - India Office Library; Bengal Hurkaru and Chronicle; India Gazette; Bengal Times (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
This collection contains copies of three English language newspapers published in India during the period 1782-1908: The India Gazette (1782-1834); The Bengal Hurkaru and Chronicle (1822-1866); and The Bengal Times (1876-1908).
Date range: 1782-1908.
Keywords: India -- History -- Sources; World history -- Sources; English newspapers -- India